Emerging and Re-emerging Virus Infections in Japan: Dengue Fever, Zika Virus Disease, and SFTS - Saijo, Masayuki (YAKUGAKU ZASSHI, 2020)
A sporadic but autochthonous dengue fever outbreak occurred in Tokyo in 2014, although the dengue virus is not in general circulation in Japan. Another lethal infectious disease, known as severe fever with thrombocytopenia syndrome (SFTS), was discovered to be endemic to Japan in January 2013. More than 400 patients with SFTS have been reported so far. The fatality rate of SFTS is approximately 30%. Also in 2014, a large outbreak of mosquito-borne Zika virus infections occurred in the South and Central parts of the American continent. Transplacental infection of a fetus with Zika virus occurs when pregnant women are infected. We cannot escape the risk of being infected with these viruses. Thus, preparedness for these emerging and reemerging virus infections is required.